SARS-CoV-2 Aiming for the Heart: A Multicenter Italian Perspective About Cardiovascular Issues in COVID-19 - Briguglio, Matteo; Porta, Mauro; Zuffada, Francesca; Bona, Alberto R.; Crespi, Tiziano; Pino, Fabio; Perazzo, Paolo; Mazzocchi, Marco; Giorgino, Riccardo; De Angelis, Giuseppe; Ielasi, Alfonso; De Blasio, Giuseppe; et al. (Frontiers in Physiology, 2020)
The SARS-CoV-2 has caused a viral pandemic whose rapid spread and the high fatality rate has put a strain on the world. Infected individuals experience unpredictable symptoms, with old age, malnutrition, and underlying cardiovascular diseases being risk factors for progressive virulence. Once transmitted, the virus affects lungs and in predisposed individuals can elicit a sequela of fatal cardiovascular consequences. As a roaming viral particle or more likely via the Trojan horse route, SARS-CoV-2 can invade different anatomical districts. From a cardiovascular perspective, COVID-19 features comprise myocardial injuries, transmigration of infected white blood cells, vasculitis-like syndromes, and atherothrombotic manifestations. Deviation of both the myocardium and brain electrograms echoes pericardial effusion, fibrotic processes, or medullary reflexes dysfunctions. Dispersed microthrombi cause ischemic damages to systemic organs and can lead to stroke. Intensive support based on early virulence indicators and patient’s severity can certainly improve clinical outcomes. Tailored treatment for reduced ejection fraction, arrhythmias, coronary syndromes, macro- and micro-thrombosis, and autonomic dysfunctions are mandatory. Confidently, evidence-based therapies for this multifaceted nevertheless purely cardiological COVID-19 will emerge after the global assessment of different approaches.